Elective caesarean sections from an evolutionary perspective - Trevathan, Wenda (Henry Stewart Talks, 2018)
The global picture of excess and insufficient caesarean sections performed, Caesarean sections in the context of evolutionary obstetrics, What are the potential downsides of a caesarean section?, The influence of caesarean sections on the baby’s acquired microbiome, The role of the mother, the clinician and the society in the decision making of opting for caesarean sections, Why do mothers and obstetricians choose caesarean sections even when not necessary?